The Effect of Using Instructional Games in Teaching Career Culture to Tenth Grade Students at South Batina Governorate in Oman - Hafidha S. AlBarashdi (Sultan Qaboos University, 2018)
This study aimed to test the effect of using instructional games in teaching career culture to tenth grade students. The sample of this study consisted of 66 female students enrolled in Asia bint Mozahem Basic School, South Batina Governorate. This sample was devided into two groups: the experimental group (N=33), and the control group (N=33). The first group learned through normal instruction styles, while the other group learned through instructional games.The results revealed that there were statistically significant differences in the career culture achievement between the two groups in favor of the experimental group.